Huge Peripheral Giant Cell Granuloma Leading to Bone Resorption: A Report of Two Cases - Elif Demirci; Ertan Yalçın; Göksel Şimşek Kaya; Sare Şipal; Ümmühan Tozoğlu (Cumhuriyet University, 2011)
ABSTRACT Although peripheral giant cell granulomas (PGCG) develop mainly within soft tissue, on rare occasions they may involve underlying bone and become visible radiologically. In such cases, the diameter of the hemorrhagic lesion rarely exceeds 20 mm, and pain is uncommon. This paper describes the successful treatment of two cases of huge PGCGs that led to alveolar bone resorption. Key words: Peripheral giant cell granuloma, bone resorption, surgery.